Effect of carbon black addition on reaction-bonded silicon carbide ceramics - Kim, J; Jun, HW; Song, H; Lee, JH; Lee, HW (TRANS TECH PUBLICATIONS LTD, 2005)
High strength reaction-bonded silicon carbide ceramics was successfully produced by reducing the amount of residual silicon and the silicon pocket size with carbon black as an additional carbon source. A prototype of wafer carrier was also produced in near-net dimension by planar contact infiltration of molten silicon into a preform joined with six pieces of simple shape by eliminating process shrinkages. Forming shrinkages were decreased to a negligible level by compression molding, while sintering shrinkage was eliminated by reactive infiltration of molten silicon.